Fisher investments on telecom - Sinton, Dan.; Teufel, Andrew S. (Hoboken, NJ : Wiley, 2011)
"The definitive guide to investing in the Telecommunications sector. Following a top-down approach to investing, Fisher Investments on Telecommunications can help readers make more informed decisions within the Telecom sector. It skillfully addresses how to determine optimal times to invest in Telecom stocks and which Telecom industries have the potential to perform well in various environments. Details how the sector works, reveals pertinent macroeconomic drivers, and presents the challenges facing companies within the sector. Segments the telecom sector by industry. Other titles by Fisher Investments: Fisher Investments on Energy, Fisher Investments on Emerging Markets, and Fisher Investments on Consumer Staples, all by Wiley. Filled with in-depth insights, Fisher Investments on Telecommunications provides a framework for understanding this sector and its industries to help you make better investment decisions now and in the future. With this book as your guide, you can gain a global perspective of the Telecommunications sector and discover strategies to help achieve your investing goals."--
Includes index.
Includes bibliographical references (p. 137-139) and index.
Keywords: Investments, Foreign; International finance; Investment analysis; Telecommunication -- Economic aspects; BUSINESS & ECONOMICS / Finance